2014
DOI: 10.1186/2193-1801-3-659
|View full text |Cite
|
Sign up to set email alerts
|

Liquid film condensation along a vertical surface in a thin porous medium with large anisotropic permeability

Abstract: The problems of steady film condensation on a vertical surface embedded in a thin porous medium with anisotropic permeability filled with pure saturated vapour are studied analytically by using the Brinkman-Darcy flow model. The principal axes of anisotropic permeability are oriented in a direction that non-coincident with the gravity force. On the basis of the flow permeability tensor due to the anisotropic properties and the Brinkman-Darcy flow model adopted by considering negligible macroscopic and microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The concept of thin-film condensation using porous structures has been reported in previous studies. [24][25][26][27][28][29] The current work validates the concept by conducting heat transfer measurements and providing visual confirmation via environmental scanning electron microscopy (ESEM). The insights gained from this work inform material design for condenser surfaces that do not require hydrophobic coating and yet achieve high phase-change heat transfer rate.…”
Section: Introductionsupporting
confidence: 55%
“…The concept of thin-film condensation using porous structures has been reported in previous studies. [24][25][26][27][28][29] The current work validates the concept by conducting heat transfer measurements and providing visual confirmation via environmental scanning electron microscopy (ESEM). The insights gained from this work inform material design for condenser surfaces that do not require hydrophobic coating and yet achieve high phase-change heat transfer rate.…”
Section: Introductionsupporting
confidence: 55%
“…Prior work has incorporated porous media and porous surfaces in condensation applications with the goal of enhancing heat transfer. For example, porous fins have been added to the outside of a tube condenser to enhance condensation heat transfer of refrigerants by 180% . Perhaps more similar to the present work, two experimental studies have applied a porous medium directly onto a condenser surface and reported heat transfer enhancements of 56% and subsequently 200% compared to filmwise condensation.…”
Section: Discussionmentioning
confidence: 62%
“…Accurate acquisition of the micro structure and flow properties of porous media is of great importance in petroleum engineering, biomedical science, micro-electronics, and composites (Hilfer and Zauner 2011 ; Sanya et al 2014 ; Tagar et al 2016 ). Thus, the pore-scale modeling, where fluid displacement is simulated in a model of porous medium, has been used as a platform to study multi-phase flow at the pore scale.…”
Section: Introductionmentioning
confidence: 99%